2017
DOI: 10.3390/rs9050437
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Resolution Repeat Topographic Surveying of Dryland Landscapes Using UAS-Based Structure-from-Motion Photogrammetry: Assessing Accuracy and Precision against Traditional Ground-Based Erosion Measurements

Abstract: Structure-from-motion (SfM) photogrammetry from unmanned aerial system (UAS) imagery is an emerging tool for repeat topographic surveying of dryland erosion. These methods are particularly appealing due to the ability to cover large landscapes compared to field methods and at reduced costs and finer spatial resolution compared to airborne laser scanning. Accuracy and precision of high-resolution digital terrain models (DTMs) derived from UAS imagery have been explored in many studies, typically by comparing im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Johnson et al (2014) also compared SfM to ALS data as a reference and found error was <13 cm for 90% of points. Gillan et al (2017) compared UAV-derived SfM measurements to manual erosion bridge measurements along topographic transects and calculated an RMSE of~3 cm. Clapuyt et al (2016) tested the reproducibility of SfM topographic datasets and found 6 cm MAE within their workflow.…”
Section: Structure From Motion: Accuracy Advantages and Recommendatmentioning
confidence: 99%
“…Johnson et al (2014) also compared SfM to ALS data as a reference and found error was <13 cm for 90% of points. Gillan et al (2017) compared UAV-derived SfM measurements to manual erosion bridge measurements along topographic transects and calculated an RMSE of~3 cm. Clapuyt et al (2016) tested the reproducibility of SfM topographic datasets and found 6 cm MAE within their workflow.…”
Section: Structure From Motion: Accuracy Advantages and Recommendatmentioning
confidence: 99%
“…The workflow implemented in this study is ideal for efficient repeat observations. This potential for producing four-dimensional data has already been realized in a range of studies [19,20,41,46,153,154]. Much of the procedure in Agisoft can be automated via custom scripts or the Batch Process option [105].…”
Section: Effective Efficient Methodology For Quantitative Repeat Phomentioning
confidence: 99%
“…Second, SfM models generated by different imaging hardware can be successfully compared at sub-decimeter resolution, even when one of the camera systems has substantial lens distortion. This means that older image sets, which might not otherwise be considered of appropriate quality for co-analysis with more recent data, should not be ignored as data sources in long-term monitoring studies.Despite these improvements in protocols for data collection and analysis, quantifying change via repeat photogrammetry remains a challenge, generally requiring manipulation of digital terrain models (DTMs) using Geographic Information Systems (GIS) [45,46]. But recent innovations in 3D differencing software, as implemented in the open-source package CloudCompare (www.danielgm.net/cc/) enable rapid, objective, and replicable quantitative differencing [47].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous recent studies have focused on the accuracy, reproducibility, and optimization of UAV surveys utilizing SfM in variable locations [32][33][34][35][36][37][38][39] and can provide some insights. The accuracy is generally considered to be affected by various parameters, including camera parameters (e.g., focal length, sensor resolution, and exposure time), acquisition parameters (e.g., flight height and ground control network), environmental parameters (e.g., solar illumination and weather), and processing settings [40].…”
Section: Results and Accuracymentioning
confidence: 99%